Simultaneous integrated boost on pathologic lymph nodes safely improves clinical outcomes compared to sequential boost in locally advanced cervical cancer: a multicenter retrospective study - Guigo, Marin; Dauda, Mohammed Sali; Lequesne, Justine; Blache, Alice; Pereira, Renata; Le Gall, Ioana; Pernin, Victor Emmanuel; Gaichies, Léopold; Clarisse, Bénédicte; Grellard, Jean-Michel; Joly, Florence; Meyer, Emmanuel; et al. (Frontiers in Oncology, 2024)
Objective: This multicenter study aimed to retrospectively evaluate the impact of high boost simultaneous integrated boost (SIB) to pathologic lymph nodes compared to Sequential boost (Seq) in patients with locally advanced cervical cancer (LACC).Materials and methods: 97 patients with pelvic and/or para-aortic (PAo) node-positive LACC treated by definitive chemoradiation were included. Two groups were analyzed: Sequential boost group and simultaneous integrated boost (SIB) group. Endpoints were Distant Recurrence Free Survival (DRFS), Recurrence Free Survival (RFS), Overall Survival (OS), locoregional pelvic and PAo control and toxicities.Results: 3-years DRFS in SIB and Seq groups was 65% and 31% respectively (log-rank p < 0.001). 3years RFS was 58% and 26% respectively (log-rank p = 0.009). DRFS prognostic factors in multivariable analysis were SIB, PAo involvement and maximum pelvic node diameter > 2cm.Adenocarcinoma histology and absence of brachytherapy tended to be prognostic factors. SIB provided the best pelvic control at first imaging with 97%. There was no significant difference in terms of toxicities between groups.Nodal SIB seems to be unavoidable in the treatment of node-positive LACC. It provides the best DRFS, RFS and pelvic control without additional toxicity, with a shortened treatment duration.